6(4x + 2) = 3(8x + 4)
Reorder the terms:
6(2 + 4x) = 3(8x + 4)
(2 * 6 + 4x * 6) = 3(8x + 4)
(12 + 24x) = 3(8x + 4)
Reorder the terms:
12 + 24x = 3(4 + 8x)
12 + 24x = (4 * 3 + 8x * 3)
12 + 24x = (12 + 24x)
Add '-12' to each side of the equation.
12 + -12 + 24x = 12 + -12 + 24x
Combine like terms: 12 + -12 = 0
0 + 24x = 12 + -12 + 24x
24x = 12 + -12 + 24x
Combine like terms: 12 + -12 = 0
24x = 0 + 24x
24x = 24x
Add '-24x' to each side of the equation.
24x + -24x = 24x + -24x
Combine like terms: 24x + -24x = 0
0 = 24x + -24x
Combine like terms: 24x + -24x = 0
0 = 0
Solving
0 = 0
Answer:
Positive 8
Step-by-step explanation:
Since they're both negative numbers and it went from -9 to -1, you had to have added a positive number to get a lesser negative number. To put it simply, if you were to subtract 8 from 9, you'd get 1.
Answer:
A is
Step-by-step explanation:
Answer:
the answer is actual B owo
First take the amount of drinks and popcorn needed then multiply the amount by the price then see if she has enough money when you finish the multiplying.